Frank Einstein and the evoblaster belt - Scieszka, Jon; Biggs, Brian (New York : Amulet Books, 2016)
Boy genius Frank Einstein finds himself in competition with his classmate and archrival T. Edison and his sign-language-speaking sidekick, Mr. Chimp, over Frank's newest invention: the EvoBlaster Belt.
Keywords: Inventors -- Juvenile fiction; Robots -- Juvenile fiction; Humorous stories; Science fiction; Inventors -- Fiction; Robots -- Fiction; Humorous stories; Science fiction; Humorous fiction; Robots -- Juvenile fiction; Robots -- Fiction; Robots -- Juvenile fiction; Inventors -- Juvenile fiction; Humorous fiction; Science fiction